Molecular hydrogen regulates the expression of miR-9, miR-21 and miR-199 in LPS-activated retinal microglia cells - Liu, Guo-Dan (International Journal of Ophthalmology Press, 2013)
AIM: To explore the potential mechanism of molecular hydrogen in the regulation of miRNA expression and signal-modulating activities. METHODS: Retinal microglia cells were activated by Lipopolysaccharides (LPS) and then treated with hydrogen-saturated medium or normal medium without hydrogen. qRT-PCR was used to detect the expression difference in miR-9, miR-21 and miR-199 between these two groups. Moreover, the expression of LPS-induced signaling proteins, including Myd88, IKK-β, NF-κB, and PDCD4, were detected by Western blotting. RESULTS: The results demonstrated a marked down-regulation of miR-9 and miR-21 and up-regulation of miR-199 by hydrogen treatment; the expression of Myd88 and IKK-β was decreased after hydrogen treatment, whereas PDCD4 was increased, and there was no significant change in NF-κB expression. CONCLUSION: The results in the present study indicate that miR-9, miR-199 and miR-21 play an important role in the anti-inflammatory regulation of LPS-activated microglia cells by molecular hydrogen, which will help to explain the protective mechanism of molecular hydrogen against inflammatory injury.